2008
DOI: 10.1017/s1049023x0000594x
|View full text |Cite
|
Sign up to set email alerts
|

Building Integrated Mental Health and Medical Programs for Vulnerable Populations Post-Disaster: Connecting Children and Families to a Medical Home

Abstract: Introduction:Hurricane Katrina, a Category 3 hurricane, made landfall in August 2005. Approximately 1,500 deaths have been directly attributed to the hurricane, primarily in Louisiana and Mississippi. In New Orleans, Louisiana, most of the healthcare infrastructure was destroyed by flooding, and >200,000 residents became homeless. Many of these internally displaced persons received transitional housing in trailer parks (“villages”) under the auspices of the [US] Federal Emergency Management Agency (FEMA).Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…Agencies responsible for disasterrelated planning should ensure that healthcare providers are able to meet the urgent mental health care needs of victims. At the same time, regional and statewide systems of mental health care should not lose sight of, and indeed should plan for, the heightened demand for longterm supplementary serv ices for vulnerable populations that is likely to follow a major public health disaster (Madrid et al, 2008). One should expect the events following a disaster, such as a hurricane, to diverge from those planned for (Quarantelli, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Agencies responsible for disasterrelated planning should ensure that healthcare providers are able to meet the urgent mental health care needs of victims. At the same time, regional and statewide systems of mental health care should not lose sight of, and indeed should plan for, the heightened demand for longterm supplementary serv ices for vulnerable populations that is likely to follow a major public health disaster (Madrid et al, 2008). One should expect the events following a disaster, such as a hurricane, to diverge from those planned for (Quarantelli, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported negative health effects in certain temporary trailer houses following hurricane Katrina, due to high indoor concentrations of formaldehyde (Maddalena et al, 2009;Madrid et al, 2008;Parthasarathy et al, 2011). For permanent houses in Japan, indoor air quality is managed by guidelines on indoor concentrations of 13 volatile chemicals and total volatile organic compounds (TVOCs) established between 1997and 2002(MHLW, 1997-2002, and by Building Codes for rates of ventilation and emission rates of formaldehyde from building materials revised at 2003(MLIT, 2003.…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of formaldehyde were found inside some of the temporary housing units built for victims of hurricane Katrina in the US in 2008, which raised the public awareness of the chemical and its potential acute health effects [3, 4]. …”
Section: Introductionmentioning
confidence: 99%